2007
DOI: 10.1017/s002531540705374x
|View full text |Cite
|
Sign up to set email alerts
|

Harmful effects of the toxic dinoflagellate Alexandrium tamarense on the tintinnids Favella taraikaensis and Eutintinnus sp.

Abstract: The effects of the exposure of two tintinnids (Favella taraikaensis and Eutintinnus sp.) to the toxic dinoflagellate Alexandrium tamarense were studied, using the non-toxic dinoflagellate Scrippsiella trochoidea as a control. The tintinnid F. taraikaensis showed backward swimming and cellular lysis after a few minutes in the presence of the toxic dinoflagellate A. tamarense in high concentration (280–700 cells ml-1). At low concentrations of A. tamarense (30–120 cells ml-1) no swimming alterations were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…The effects of Alexandrium exudates on the tintinnid ciliate F. ehrenbergii were previously studied by Hansen (Hansen, 1989), Hansen et al (Hansen et al, 1992) and Fulco (Fulco, 2007) (Table II), who observed a recurring behavioral response: reversal of ciliary movement and continuous swimming backwards with subsequent death. Using the same experimental design, our experiments indicated a reduction in survival after exposure to exudates, with no apparent change in swimming behavior Table I. apart from progressive lethargy.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Alexandrium exudates on the tintinnid ciliate F. ehrenbergii were previously studied by Hansen (Hansen, 1989), Hansen et al (Hansen et al, 1992) and Fulco (Fulco, 2007) (Table II), who observed a recurring behavioral response: reversal of ciliary movement and continuous swimming backwards with subsequent death. Using the same experimental design, our experiments indicated a reduction in survival after exposure to exudates, with no apparent change in swimming behavior Table I. apart from progressive lethargy.…”
Section: Discussionmentioning
confidence: 99%
“…Resale or republication not permitted without written consent of the publisher 1992, Fulco 2007). Turner et al (1998) compiled data on the effects of Alexandrium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Among the initial sublethal effects on tintinnids are alterations of swimming speed and pattern, including backwards swimming (Hansen 1989, Hansen et al 1992, Fulco 2007. After a few minutes of exposure, cells tend to swell and subsequently lyse.…”
Section: Introductionmentioning
confidence: 99%
“…For most of these compounds both the chemical structure and toxicity are well known, mainly because they are toxic to mammals and are therefore of concern to human health [ 7 ]. These compounds have been regarded as putative “defensive compounds” because of their high potency in mammalian systems, and they are also suspected to be allelopathic agents responsible for the deleterious effects on metazoan and protistan grazers and algal competitors [ 8 11 ]. Whereas the defensive role of the known phycotoxins may remain valid at least in some cases involving metazoan grazers [ 12 ], with respect to protistan targets, it is now quite clear that neither PSP toxins nor spirolides are involved in the observed negative effects [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%